نظرية ومنهجية التربية البدنية والرياضية - كرميش ، عبدالمالك فريد (Mohamed Boudiaf University of M'Sila, 2025)
الملخص : بالعربية : يعد مقياس نظرية ومنهجية التربية البدنية والرياضية ركيزة أساسية في تكوين طلبة علوم وتقنيات النشاطات البدنية والرياضية، حيث يهدف إلى تزويدهم بالأسس العلمية، المعارف النظرية، والقواعد المنهجية لبناء وتخطيط دروس التربية البدنية والتدريب الرياضي، وضمان تحقيق الأهداف التربوية، الحركية، والبدنية، مع تطبيق مبادئ التدريب وطرق التدريس الحديثة. . Searchlight in English The subject of Physical Education and Sports Theory and Methodology is a fundamental pillar in the training of students of Physical and Sports Activities Sciences and Technologies. It aims to provide them with the scientific foundations, theoretical knowledge, and methodological rules for building and planning physical education and sports training lessons, and to ensure the achievement of educational, motor, and physical goals, while applying modern training principles and teaching methods.
Keywords: التخطيط; التدريس; المقاربة بالكفاءات